Identification of the barley phyllosphere and the characterisation of manipulation means of the bacteriome against leaf scald and powdery mildew - Gravouil, Clement (2012)
In the context of increasing food insecurity, new integrated and more sustainable crop protection methods need to be developed. The phyllosphere, i.e. the leaf habitat, hosts a considerable number of microorganisms. However, only a limited number of these are pathogenic and the roles of the vast majority still remain unknown. Managing the leaf-associated microbial communities is emerging as a potential integrated crop protection strategy. This thesis reports the characterisation of the phyllosphere of barley, an economically important crop in Scotland, with the purpose of developing tools to manipulate it. Field experiments were carried out to determine the composition of the culturable bacterial phyllosphere. The leaf-associated populations were demonstrated to be dominated by bacteria belonging to the Pseudomonas genus. Two bacterial isolates, Pseudomonas syringae and Pectobacterium atrosepticum, hindered the growth of Rhynchosporium commune, the causal agent of the leaf scald, but promoted the development of powdery mildew symptoms, caused by Blumeria graminis f.sp. hordei. However, using a molecular fingerprinting technique, namely T-RFLP, the global community was shown to be significantly richer and more diverse than indicated by the culture-based methods, thus increasing the complexity of interactions taking place in the phyllosphere. Various factors were found to affect the structure of the phyllobacteria significantly. Under controlled conditions, a root-associated symbiont, Piriformospora indica, was shown to increase the plant fitness and shift the abundance of the most common bacteria. In the field, both agro-chemical treatments tested, conventional fungicide and an elicitor mixture, increased the bacterial diversity, but fungicide application resulted in a higher yield and better protection against diseases. Finally, the plant genotype also affected the phyllosphere structure. Mutations in the leaf epicuticular waxes led to significant changes in the bacterial diversity and differentially affected disease in the field. A negative correlation between bacterial diversity and scald infection was also observed.